Clashes and compromises: Investment policies in tourism destinations - Guido Candela; Massimiliano Castellani; Maurizio Mussoni (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
The authors solve a linear problem where a potential conflict between two agents (Destination manager and Firm) arises in a tourism destination. The Destination manager has to choose how to allocate limited resources (capital and land) between either second homes or hotels. This conflict stems from the assumption of agents who have different linear preferences with respect to the allocation of limited resources. As a solution to this policy problem the authors consider three different policies: no intervention (laissez faire), taxation and temporary de-taxation policy. Comparing these different policies, they show that a compromise solution (internal solution), which results from the de-taxation policy, may be preferred by both agents over the clash of interests outcomes (corner solutions). Thus, the authors show that in a framework of "conflict" between agents a compromise solution may be preferable to both the absence of public intervention and the imposition of a tax by a public policy maker who has the discretionary power to regulate conflicts.
Keywords: D74; G11; L83; R52; 330; conflict resolution; investment decisions; tourism and land use; Tourismusregion; Destinationsmanagement; Tourismuspolitik; Investitionspolitik; Bodennutzung; Konflikt; Steuerpolitik; Theorie